Using pledges to improve the effectiveness of environmental information campaigns: The case of biowaste recycling - Eduard Alonso-Paulí; Pau Balart; Lara Ezquerra; Iñigo Hernandez-Arenaz (Proceedings of the National Academy of Sciences, 2025)
Through a field study (N = 1,519) that uses a technology to record real-time data on waste sorting, we find that offering the opportunity to sign a pledge increases the effectiveness of an environmental campaign. With a timespan of over four years, the pledge increased waste sorting participation by 4.55 to 5.10 percentage points (SD = 0.1997). The effect is greater immediately after the campaign (around 9 to 10 pp during the first 15 wk), but it remains sizable and statistically significant 150 to 210 wk after signing (3.11 to 4.45 pp).